The muscle to bone axis (and viceversa): An encrypted language affecting tissues and organs and yet to be codified?. (March 2021) - Bosco, Francesca; Musolino, Vincenzo; Gliozzi, Micaela; Nucera, Saverio; Carresi, Cristina; Zito, Maria Caterina; Scarano, Federica; Scicchitano, Miriam; Reale, Fabio; Ruga, Stefano; Maiuolo, Jessica; Macrì, Roberta; et al.
Graphical abstract: Abstract: Skeletal muscles and bone tissue form the musculoskeletal apparatus, a complex system essential for the voluntary movement. The loss of muscle mass and muscle strength is often associated with a loss of bone mass, in a "hazardous duet" which implies the co-existence of sarcopenia-osteoporosis and exposes patients to a deterioration in quality of life and increased mortality. From the mechanostat theory to the recent definition of the osteosarcopenia syndrome, many aspects of muscle-bone interaction have been investigated in recent decades. The mechanical interaction is now accepted, considering the close anatomical relationship between the two tissues, however, much remains to be discovered regarding the biochemical muscle-bone interaction. Skeletal muscle has been defined as an endocrine organ capable of exerting an action on other tissues. Myokines, bioactive polypeptides released by the muscle, could represent the encrypted message in the communication between muscle and bone. These two tissues have a reciprocal influence on their metabolisms and respond in a similar way to the multiple external factors. The aim of this review is to stimulate the understanding of the encrypted language between muscle and bone, highlighting the role of catabolic pathways and oxidative stress in the musculoskeletal apparatus to elucidate the shared mechanisms and the similarity of response to the same stimuli by different tissues. Our understanding of muscle-bone interactions it could be useful to identify and develop new strategies to treat musculoskeletal diseases, together with pharmacological, nutritional and exercise-based approaches, which are already in use for the treatment of these pathologies.